Convective precipitation simulated with ICON over heterogeneous surfaces in dependence on model and land-surface resolution - Singh, Shweta (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2021)
The impact of land-surface properties like vegetation, soil type, soil moisture, and the orography on the atmosphere is manifold. These features determine the evolution of the atmospheric boundary layer, convective conditions, cloud evolution and precipitation. The impact of model grid spacing and land-surface resolution on convective precipitation over heterogeneous surfaces is investigated using ICOsahedral Nonhydrostatic (ICON) simulations within the framework of the HD(CP)2 project.